2020
DOI: 10.1002/bdm.2216
|View full text |Cite
|
Sign up to set email alerts
|

Construal level theory and risky decision making following near‐miss events

Abstract: Near-miss events, which occur when failure is avoided by chance, can lead to subsequent risky decisions due to base-rate neglect. According to construal level theory, a lower level construal increases the neglect of base rates by giving more weight to case-specific information. In four studies, I empirically test the hypothesis that lowlevel construals moderate evaluations and decisions following near-miss events by increasing the reliance on case information. In Study 1, I find that a higher construal correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(44 reference statements)
0
7
0
1
Order By: Relevance
“…In detail, the effect of text is more prominent when it is from the government source, and the effect of the loss frame will be strengthened when it is from the NGO source. According to the construal level theory (CLT), an individual’s level of abstraction systematically influences cognitive processing, and abstraction often makes mental representations more inclusive and focused on central characteristics [ 67 ]. Different from images focusing on concrete and low-level details, written texts are more abstract and with greater attention to higher-level concepts.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the effect of text is more prominent when it is from the government source, and the effect of the loss frame will be strengthened when it is from the NGO source. According to the construal level theory (CLT), an individual’s level of abstraction systematically influences cognitive processing, and abstraction often makes mental representations more inclusive and focused on central characteristics [ 67 ]. Different from images focusing on concrete and low-level details, written texts are more abstract and with greater attention to higher-level concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, individuals with this near-miss information make riskier future decisions than those without such information. Subsequent studies have replicated this effect and have demonstrated the influence of other factors on risky decision-making following such events (Kirshner, 2021;Paine et al, 2020). From an individual perspective, near-misses have been studied as potential learning opportunities in settings such as natural disasters (Tinsley et al, 2012) and inadequate safety procedures (Dillon et al, 2016;Dillon & Tinsley, 2008).…”
Section: Operational Disruption and Nearmiss Eventsmentioning
confidence: 95%
“…In some cases, such events may even prompt managers to make riskier future decisions. Several studies (Dillon & Tinsley, 2008; Kirshner, 2021; Tinsley et al, 2012) have documented the presence of a systematic bias when confronted with near‐miss events: managers exhibit a preference for close‐call successes, and this preference subsequently leads to suboptimal and riskier decisions. Recent papers have called for an enhanced understanding of outcomes and near‐misses in supply chains to improve learning and risk management (Azadegan et al, 2019; Habermann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Supply chains are increasingly global (spatial distance), when (or if) modern slavery presents itself is uncertain (temporal distance), exploited workers experience circumstances that are unfamiliar to most western managers (social distance), and managers largely lack experience with exploitation and the systems that encourage it (hypothetical distance) (Trope, Liberman & Wakslak, 2007; Cantor & McDonald, 2009). High psychological distance has significant consequences for decision‐making as it can encourage individuals to rely more on predictions (rather than data), be more risk averse, or believe events are less likely to occur (Soderberg et al, 2014; Liberman & Trope, 2014; Kirshner, 2021). Firms that are more psychologically distant from modern slavery risk, for example, may manage risk in ways that fail to address its complexities.…”
Section: Introductionmentioning
confidence: 99%